Protective Effect of Eggshell Powder on the In Vitro Titer Stability of Immunoglobulin Y - Li, Yi; Xiong, Huan; Zhang, Zhi; Jian, Xiaohong; Li, Zaixin (International Journal of Public Health and Medical Research, 2026)
Objective Aiming at the problem that immunoglobulin Y (IgY) is susceptible to acid-base, temperature and enzymatic hydrolysis in vitro, resulting in reduced titer, this study was designed to systematically evaluate the protective effect of eggshell powder on the titer stability of IgY under different pH, temperature, time and packaging conditions, and to verify its anti-digestive ability in simulated gastric fluid. Methods Using IgY as the research object and eggshell powder as the protective agent, multi-gradient experiments were set up: the titer changes were investigated at different pH (1, 3, 7.8), temperatures (-20, 4, 24, 37℃) and storage time (0-360 d); the effects of conventional packaging and vacuum packaging were compared; and incubation in simulated gastric fluid was performed for 0–60 min. The IgY titers of each group were determined by indirect enzyme-linked immunosorbent assay (ELISA), and the retention rates were calculated. Results Compared with the control group, eggshell powder significantly increased the titer retention rate of IgY under strong acid condition (pH = 1.0) (P0.05). After treatment in simulated gastric fluid for 60 min, the antibody retention rate reached 95.6% at 60 min, showing excellent acid resistance and anti-enzymolysis properties. Conclusion Eggshell powder can effectively maintain the titer stability of IgY in complex in vitro environments and simulated digestive juice, indicating its application potential as a natural oral delivery carrier.